The Meaning of the Principle of Material Legality in the Reform of Indonesian Criminal Law - Itok Dwi Kurniawan (IJOLARES : Indonesian Journal of Law Research, 2023)
The principle of legality is a very important principle in criminal law. The principle of legality plays an important role in the enactment of material criminal law rules and is the basis for the validity of acts categorized as criminal acts. The purpose of this study is to determine the meaning of the principle of material legality in the reform of Indonesian criminal law. This article was prepared using the normative legal research method. The results showed that the reform of criminal law with the enactment of Law Number 1 Year 2023 on the Criminal Code did not only change the formulation of the principle of legality substantially, but changed the formal principle of legality which was originally far from the sense of public justice, expanded into a material principle of legality that better guarantees the sense of public justice. This article will discuss the material legality principle as a renewal of the formal legality principle, which aims to expand the reach of the legality principle in providing protection to the community from the negative consequences of criminal acts.